CGIAR research on agricultural insurance: Past achievements and future research priorities - Kramer, Berber; Ceballos, Francisco; Hazell, Peter B. R.; Timu, Anne G. (International Food Policy Research Institute, 2021)
KEY MESSAGES • A recent external review of IFPRI’s research on agricultural insurance found that, since 2009, IFPRI has made important contributions to the literature on factors constraining farmers’ demand for agricultural insurance and on gender inclusiveness of insurance and, since 2015, has focused more specifically on developing new forms of insurance that can reduce basis risk at the farm level and make insurance more attractive to farmers. • IFPRI’s work on flexible insurance contracts, picture-based insurance, and bundling agricultural insurance with credit, seeds, and other agricultural services shows that well-designed insurance can significantly improve on standard index products, increase demand among smallholders, and lead to greater use of bundled inputs like improved seeds and climate-smart farming practices. • ILRI’s long-term success with its index-based livestock insurance (IBLI) product illustrates that an action-oriented approach aimed at working with strong implementing partners on the ground ensures that, when a product is successful, it has the potential to scale up quickly, leading to significant development impacts. • Important knowledge gaps that warrant further CGIAR research include: 1) segmenting product design and marketing strategies for different target groups, such as sustainable commercial insurance and inclusive insurance; 2) the value and optimal design of programs and policies to remove tail-end catastrophic risks, and of insurance more broadly within a more holistic risk management framework; and 3) cost-benefit analyses around the net social benefits of insurance subsidies, and how these subsidies can best be designed and targeted to achieve their purposes.